Cover JGEET Vol 03 No 04 2018 - (J. Geoscience Eng. Environ. Technol.), JGEET (UIR PRESS, 2018)
This Volume Consists of Research Article as follow: Cross plot Analysis of Rock Properties from Well Log Data for gas detection in Soku Field, Coastal Swamp Depobelt, Niger Delta Basin Settings Characteristics of Groundwater on the Eastern Slope of Mount Ciremai, Kuningan Regency, West Java, Indonesia Settings Petrography, Geology Structure and Landslide Characterization of Sumatra Fault Deformation: Study Case In Km 10-15 Highway, Koto Baru Sub District, West of Sumatra Settings Groundwater Quality Assessment for Drinking Purpose in Gulistan-e-Johar Town, Karachi, Pakistan Settings Festivals and deterioration of aquatic environment: A case study of Idol immersion in Tapi River, India Settings Interpretation of 2D-Subsurface Resistivity Data in The Iron Ore Prospect Area of Eastern Binangun Coastal, Regency of Cilacap, Central Jawa Settings Arsenic survey in Dried Sediments of Maharlu Saline Lake Settings Groundwater exploration using Vertical Electrical Sounding (VES) Method at Toro Jaya, Langgam, Riau Settings Gold mineralization in the Neo-Tectonic Region of Honje Formation and Cipacar Formation